Technodiversity and urban forests in Belo Horizonte: a strategy for adaptation to the urban context - Carvalho Filho, Luciano Goulart de; Rena , Natacha Silva Araújo (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective – Provide a theoretical basis for improving urban reforestation projects in Belo Horizonte (Minas Gerais, Brazil), demonstrating the potential of diversifying planting techniques to reduce the time required for the expected ecosystem services to return and to increase public spending efficiency.Methodology – Different planting methods were analyzed, such as the Miyawaki Method, direct seeding through “muvuca de sementes,” and half-moon planting, in comparison with the practices adopted in the Montes Verdes project by the Belo Horizonte City Hall.Originality/Relevance – The research highlights the opportunity to strengthen urban forests implemented by the public sector through technodiversity, considering the singularity of the transition between the Cerrado and Atlantic Forest biomes in the municipal territory, as well as the need to expand strategies currently centered on Atlantic species and silviculture-like methods.Results –It was found that the adoption of multiple techniques can reduce seedling mortality, minimize maintenance costs, increase the resilience of plantations against invasive grasses and fires, and accelerate the provision of ecosystem services such as microclimatic regulation and shading.Theoretical/Methodological Contributions – The study reinforces the concept of technodiversity as a methodological framework for urban reforestation, showing that combining techniques adapted to the local context increases both the ecological and economic efficiency of urban forests.Social and Environmental Contributions – In addition to environmental gains, the study points to relevant social benefits, such as fostering community engagement in planting and management processes, strengthening socio-environmental awareness, and valuing biocultural diversity as a pillar of urban sustainability.
Keywords: Urban forests; Technodiversity; Reforestation